The analysis of the Process of Counselling and Psychotherapy - Ezy Maulany, Ledita; Mudjiran, Mudjiran; Sukma, Dina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
Today, many of us humans do not realize the importance of socializing, needing other people, medication, and so on. The things mentioned earlier can happen partly because we humans sometimes think that we can and are capable, even though this perception is not always true. In the world of counseling, this is said to be a human being who is KES-T (Effective Daily Life Disturbed). Furthermore, to help people with KES-T, counseling and psychotherapy are professional services that can help people overcome them. If you look at it in general, the process of counseling and psychotherapy is not much different, but if you look more closely, the two have differences in terms of concepts and different objects of practice. The method used in this article is an analysis of literature studies in which the collection of information regarding the counseling and psychotherapy process comes from all types of reading sources, both direct and indirect written sources such as printed or electronic reading sources